The Influence of Social Media Marketing Exposure and Email Blast Exposure on Brand Loyalty of Grab Application - Safira Nurin Aghnia; Tandiyo Pradekso; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
This study aims to explain the influence of social media marketing exposure and email blast exposure on brand loyalty of Grab application. This research is quantitative studies, with the theory that it used are Honeycomb Model and Theory of Flow that combines a non-probability sampling method with accidental sampling. The total of the respondents around 166, who lived in Indonesia's big cities and use email and social media to receive, see, and experience updated campaign information from Grab application. The results of the hypothesis tests using simple linear regression technique shows that there is no influence of social media marketing exposure on brand loyalty, meanwhile the second hypothesis shows that there is an influence of email blast exposure on brand loyalty with the significance value of (0,050). The result suggest that Grab Indonesia can implements this marketing communication ways specifically in using email blast exposure in strengthening their brand loyalty.